Caracterização termo-óptica de polímeros em função da temperatura via espectroscopia de lente térmica e espelho térmico - Aréstegui Sierra, Odón (2011)
In this work the time resolved thermal lens and thermal mirror methods are combined with interferometric technique, the thermal relaxation calorimetry, DSC and dilatometry techniques to determine the thermo physical properties of polymers as a function of temperature up to the glass transition region. Thermal diffusivity, thermal conductivity, linear thermal expansion coefficient and thermal coefficient of electronic polarizability were determined. The results showed the ability of both the thermal lens and thermal mirror techniques and the interferometric method as remote techniques to perform the measurements very close to the phase transition region which unlike conventional calorimetric methods these techniques provide absolute values for the measured physical quantities and is advantageous when low temperature scanning rate is required. Additional information on the physical parameters of the samples was obtained by using the combination of the thermal lens and thermal mirror techniques.